Interaction of vitamin D, homocystein and dental diseases - Ye. O. Karpun; Yu. V. Karpenko; M. V. Parchenko; O. A. Bihdan (Zaporozhye State Medical University, 2020)
The 1,2,4-triazole nucleus is resistant to metabolism and is an important pharmacophore; it can increase solubility and improve the pharmacokinetic and pharmacodynamic profile of drugs. Domestic scientists pay much attention to the heterocyclic 1,2,4-triazole system. A two-component system comprising "EC 2.7.13.3 Histidine kinase" and a variable response protein may be crucial for the virulence of some fungal strains, which are often the cause of candidiasis in immunocompromised individuals. Because of the fact, that humans lack this two-component system, it may be a good target for antimicrobials to treat candidiasis. The purpose of the study was to carry out a molecular docking and evaluate the bioavailability of S-alkyl derivatives of 5-(3-fluorophenyl)-, 5-(5-bromofuran-2-yl)- and 5‑((((3-(pyridin-4-yl)-1H-1,2,4-triazole-5-yl)thio)methyl)-4-methyl-4H-1,2,4-triazole nucleus in silico by methods promising as objects of biological properties for inhibitors «EC 2.7.13.3 Histidine kinase». Materials and methods. The synthesis of compounds is carried out according to the well-known method. A virtual screening of compounds was performed using a computer software program PASS. Molecular docking was performed using Autodock 4.2.6. The screening was performed on the crystallographic structure of the enzyme "EC 2.7.13.3 Histidine kinase" (1A0B). Results. Analysis of the results of a computer prediction demonstrates the prospect of finding inhibitors of histidine kinase, cytidine deaminase, STAT transcription factor, alkaline phosphatase, CYP2C9, insulin, nootropic and diuretic action, antituberculous activity in a number of these compounds. Molecular docking has shown a high affinity of the selected compounds to the enzyme "EC 2.7.13.3 Histidine kinase" with the corresponding values. The interaction of the ligand with the active center of the enzyme is quite complex and is mainly provided by van der Waals and π-bonds with water molecules and amino acid residues of the enzyme. An important point for binding to the enzyme is the presence of Sulfur atoms in the molecules of the test compounds. Based on the above, it is the promising structural modification of the nucleus by the position of the Sulfur atom. Conclusions. Data from a computer prediction indicate the prospect of searching among the two areas of bioregulators that could be potential histidine kinase inhibitors and diuretic agents. Molecular docking has shown a high affinity of the selected compounds for the "EC 2.7.13.3 Histidine kinase" enzyme, which is provided with van der Waals and π‑bonds with water molecules and amino acid residues of the enzyme.